Harmonized physical and technical training model for swimming sport elite tested in basic training mesocycle - Arishin, A. V.; Akhmetov, S. M.; Pogrebnoy, A. I. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to rate benefits of the new movement biomechanics prioritizing harmonized physical and technical training model for the swimming sport elite.